PENGARUH PELATIHAN KETERAMPILTERHADAP KEMAMPUAN MENGARANG SISWA SMA The Effect of the Training of Process Skill on The Writing Ability of The - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
The purpose of this study was to measure the effect of training of process skill on knowledge and skill of writing of senior high school students.The subjects were 70 students. They were randomly selected in random and grouped into two groups. The experimental group consisted of 35 students and controlled group consisted of 35 students.The experimental group was trained for one week but the control group was not.Both groups at the same time, were given a test on the knowledge of writing in the form of multiple choice with 50 items . They were also asked to perform their ability in writing about one of the given topics.The test on writing skill was scored by three scorers based on the scoring guidance given.The data were analyzed by t-test and the results showed that there were a significant differences between the experimental group and the controlled with t= 15.971 and p= < 0.01 for the knowledge of writing, 10.901 and p= < 0.01 for the scores. f writing skill.From the data above, it was clear that the training of process skill affected the knowledge and the skill of writing of the senior high school students.